Process Aspect of Educational Services: From Concept Development to Implementation, Evaluation, and Post-Event Activities - Razdevšek, Lana; Harambašić, Edin; Marič, Miha (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
This project paper examines the process aspect of organizing professional educational events – from the initial idea, planning, and implementation to evaluation and post-event activities. The purpose of the research is to analyze the organizational processes involved in conducting professional educational programs within the company Skupina SIMIČ & PARTNERJI d.o.o., which organizes various professional trainings and conferences through the Tax Education Institute. Special emphasis is placed on identifying key stakeholders, defining responsibilities, coordinating activities, and ensuring the timely execution of individual tasks. The research is based on a qualitative case study approach. Data collection is planned through a semi-structured interview with a company representative actively involved in organizing educational events. The analysis will focus on identifying key organizational processes, challenges, and best practices related to the implementation of professional educational events. The findings emphasize the importance of effective project management, stakeholder communication, digital support, and systematic activity planning. The paper also highlights the importance of adapting to modern educational formats, such as digital and hybrid learning models. Based on the research findings, recommendations for improving the organization of educational events and enhancing process management practices will be developed.